Gender differences in agricultural productivity: a survey of empirical evidence - Quisumbing, Agnes R. (International Food Policy Research Institute, 1995)
This paper reviews the econometric evidence on gender differences in agricultural productivity. It provides a methodological overview and a critique of (1) production function-based estimates of technical and labor productivity differences by gender, (2) individual (gender-disaggregated) labor supply and earnings functions and (3) studies of the determinants of technological adoption. The review finds that (1) in general, male and female farmers are equally efficient as farm managers. Women farmers' lower yields are attributable to lower levels of inputs and human capital than men. However, the use of coefficients estimated from these studies for simulation exercises may not be valid if endogenous input choice is not considered; (2) returns to schooling for both men and women are significant in dynamic agricultural settings where modern technologies have been introduced. Returns to an additional year of women's education range from 2 to 15 percent, which compares favorably with those of men; and (3) farmers with more education are more likely to adopt new technologies. Providing universal primary education also stimulates early adoption by female farmers, whom other women are more likely to imitate. Farmers with more land and farm tools are also more likely to adopt new technologies. To the extent that women farmers may have less education, less access to land, and own fewer tools, they may be less likely to adopt new technologies.